Efeitos de processo educativo nutricional sobre o nível de conhecimento de escolares na prevenção e controle da obesidade infantil - Picerni, Cristiane Mara Cedra [UNIFESP] (2016)
Obesity is a worldwide prevalence disease regarded as a 21st century epidemic. It decreases the quality of life and reduces from five to eight years the average of life expectancy. The sedentary lifestyle of children, whom spend many hours watching TV and playing video games, associated with large availability of high calorie foods, encourages and increases obesity in children. Changes in lifestyle, including physical exercises and clinical, nutritional and psychological monitoring, are considered effective strategies for improving nutritional staus, body composition, weight loss and healthy food consumption. As overweight children are more likely to become obese in their adulthood, it is essential to develop strategies at school since it is an ideal place to work nutritional education activities. The aim of this study was to apply an educational tool to verify the improvement of children knowledge level in the area of healthy nutrition. In addition, the study aimed at the prevention and control of obesity in children. The protocol was developed by the Obesity Study Group of UNIFESP and was based on the book that comprises nutritional education activities. The research was performed on 49 students from one private school in São Paulo, whom underwent a nutritional intervention protocol in their curriculum during four months. The main finding was that the intervention model has shown significant improvements in the level of nutrition knowledge, favoring the control of obesity and its comorbidities in children.